2021
DOI: 10.7554/elife.57241
|View full text |Cite
|
Sign up to set email alerts
|

The dimeric Golgi protein Gorab binds to Sas6 as a monomer to mediate centriole duplication

Abstract: The duplication and 9-fold symmetry of the Drosophila centriole requires that the cartwheel molecule, Sas6, physically associates with Gorab, a trans-Golgi component. How Gorab achieves these disparate associations is unclear. Here we use hydrogen-deuterium exchange mass spectrometry to define Gorab's interacting surfaces that mediate its sub-cellular localization. We identify a core stabilization sequence within Gorab's C-terminal coiled-coil domain that enables homodimerization, binding to Rab6, and thereby … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…It is interesting to note that GORAB oligomerization is necessary for binding to vimentin IFs, and it is also required for the formation of TGN-associated GORAB domains involved in COPI vesicle traffic (Witkos et al, 2019). Hence, GORAB oligomerization may control the various functions of the protein, as proposed by Fatalaska et al, who found that centriolar GORAB is present as a monomer, whereas it is a dimer at the TGN (Fatalska et al, 2021). Interestingly, the K190 deletion, a causative mutation in GO that disrupts GORAB olgomerisation, abolishes both TGN domain formation and IF binding, raising the possibility that IF binding could also be disrupted in GO.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…It is interesting to note that GORAB oligomerization is necessary for binding to vimentin IFs, and it is also required for the formation of TGN-associated GORAB domains involved in COPI vesicle traffic (Witkos et al, 2019). Hence, GORAB oligomerization may control the various functions of the protein, as proposed by Fatalaska et al, who found that centriolar GORAB is present as a monomer, whereas it is a dimer at the TGN (Fatalska et al, 2021). Interestingly, the K190 deletion, a causative mutation in GO that disrupts GORAB olgomerisation, abolishes both TGN domain formation and IF binding, raising the possibility that IF binding could also be disrupted in GO.…”
Section: Resultsmentioning
confidence: 97%
“…GORAB is also present at the centrioles, where it binds the cartwheel protein SAS-6 (Kovacs et al, 2018). GORAB binds SAS-6 as a monomer, whereas at the TGN it is present as a dimer (Fatalska et al, 2021). The function of GORAB at the centriole is unclear, but it may act as a physical scaffold, analogous to its proposed function at the TGN.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are suggestions they interact. In Drosophila , monomeric Gorab localises to centrioles ( Fatalska et al, 2021 ; Kovacs et al, 2018 ), and the cilia of gorab null sensory neurons have disorganised ciliary rootlets and disrupted ninefold radial symmetry ( Kovacs et al, 2018 ). In these studies, Gorab function in Golgi trafficking and ciliogenesis can be separated suggesting the compartments are not directly interacting.…”
Section: The Golgins Caught At the Intersectionmentioning
confidence: 99%
“…[ 130 ] In vitro experiment showed that Gorab binds to the C‐terminal region of Sas6 dimer via its C‐terminal part, and its N terminus extends away from Sas6. [ 130,131 ]…”
Section: The Nine‐fold Symmetry Of Centriolementioning
confidence: 99%